IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (ADD) DI KECAMATAN MARAWOLA KABUPATEN SIGI - Syamsidar, Syamsidar (Katalogis, 2015)
This study aims to determine the extent of implementation of the Village Fund allocation policy in District Marawola Sigi using Theory of Edward III, namely Communications, Disposition, Bureaucratic Structure and Resources. This study used a qualitative approach. Location research and key informants conducted purposive. data were analyzed in stages based on the data information from the informant obtained through observation, interviews and documentation.The results showed that the Village Fund Allocation Policy Implementation in District Marawola Sigi running less effective. This is seen in the Dimensions of Communication where aspects of policy dissemination Village Fund Allocation In District Marawola Sigi less implemented by the Village. Inadequate Resources dimensional fine views of human resources and infrastructure. Dimensions disposition in this case managers and community commitment in the implementation of the Village Fund Allocation going well, because the proposal is not based on people's needs. Bureaucratic structures seen on the dimensions of the mechanism of managing the implementation of a whole series of stages of the management of the Village Fund Allocation going well, because the preparation of development programs financed by the Village Fund Allocation prepared by the sub-district instead of the village.